PERBANDINGAN SISTEM KEPOLISIAN DI BEBERAPA NEGARA - Rosidah, Nikmah (JURNAL KOMPILASI)
The study examines the comparative police system in several countries. Research using normative judicial approach. The result showed that the current Indonesian police, Indonesian police have moved into the civilian who gives direction in which society is do thick directional approach in every chapter and chapters in the police law. Because she had seen the condition was reversed in the new order perlod that is long enough, so that one of the demands for reform in 1998 was repositioned as a whale police force, there is now nearly ideal system expected by police its own the military, and the police need to do now is to increase its human resources as well as to make improvements to the fullest.